A path unenvisaged to a destination unintended: A collaborative autoethnographic account of becoming a community of practice in an HEI - Excell, L.; Dixon, K.; Linington, V.; Mathews, C. (South African Journal of Higher Education, 2016)
In this paper we explore how a disparate group of predominately foundation phase teacher educators unintentionally, over a period of time, came together to form a strong community of practice (CoP). Voluntary involvement in a research project positioned this group of lecturers in unaccustomed roles and necessitated that they engage with each other in a variety of ways to meet project outcomes. New relationships developed as people took on different roles and new responsibilities emerged as the group faced challenges. As this was a subjective interrogation of our experiences, a research method such as autoethnography where we could focus on the experience and processes of becoming a CoP, rather than the outcomes of the research itself, seemed appropriate. We outline our understandings of a CoP and show how, through a critical self-reflective process, we were able to strengthen both our teaching and research practices in a Higher Education Institution (HEI). The strengthening occurred, in part, due to the formation and development of this CoP.